Investigation of administrative obstacles to family physician program in urban areas of Iran - Javad Javan noughabi; Saeed Hosseini (Gonabad University of Medical Sciences, 2017)
Health is regarded as one of the basic rights of each person in society; so governments are obligated to provide it equally for everyone. The best way to achieve this goal is the establishment of health insurance with the orientation of family physician and the strategic referral system. Yet, such programs will not be successful without encouraging people to participate and changing social behaviors. The aim of the present study was to investigate the administrative obstacles and problems to family physician program in urban areas of Iran. This study was a qualitative research conducted. A purposive sampling method was employed and the data were gathered via semi-structured interview with open-ended questions and document examination. All the interviews were recorded digitally and immediately transcribed verbatim. They were finally analyzed based on framework analysis. The participants' detailed descriptions showed that systemic, environmental, and human related factors were the main obstacles to the implementation of family physician plan. Since the success and performance of each program effectively cannot be obtained without people's acceptance and collaboration, the necessity of training and giving information rapidly and timely to the residents in urban areas is felt more than ever. Also, making authorities aware of the obstacles expressed by people can be helpful in harmonizing the program with people's requests; and can result in overcoming the challenges and obstacles facing the program.